Task Analysis for Developing Maintenance and Assembly VR Training Simulators. (January 2013) - Yuviler-Gavish, Nirit; Krupenia, Stas; Gopher, Daniel
Task analysis for the development of a virtual reality (VR) training system requires analysis and identification of the operator's interactions with the real-world system and of the objectives of training and the trainee's skill acquisition requirements. A task analysis approach for developing VR training simulators is presented that is based on analyzing the technology and training requirements concurrently. This approach is compared with traditional approaches for system development, with examples provided from the development of a VR training simulator for industrial maintenance and assembly tasks.